A proposed new development of Teresa District Jail - Cruz, Evitha Peron Gajutan (Manila : National University, 2018)
It is a study about a correctional facility that focusses and added the proper or the needs of a jail from the Bureau of jail management and penology and the United Nation standard minimum rules for the treatment of the prisoners.
Chapter 1. The problem and its setting -- Chapter 2. Review of Related literature -- Chapter 3. Research methodology -- Chapter 4. Data gathering, collation and analysis data -- Chapter 5. Design development -- Chapter 6. Translation -- Bibliography.
Includes bibliographical references.
Keywords: CORRECTIONAL FACILITY